The Inclusive Society? - Levitas, R. author. aut Link
XI, 223 p.
Keywords: A topical critical examination of the idea of social exclusion and the new political language of social cohesion, community, stakeholding and inclusion. The Inclusive Society? examines the actions and rhetoric of the Labour Party and Labour Government under Tony Blair's leadership. It identifies three different discourses of social exclusion. Using this model, it explores views of inclusion put forward by Will Hutton and other stakeholders, by communitarians including Etzioni and Gray, and by the Labour Party from the Borrie and the Commission on Social Justice to Blair and the Social Exclusion Unit.